1999
DOI: 10.1177/154596839901300103
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutics in the Management of Spasticity

Abstract: Spasticity is commonly defined as a velocity-dependent increase in tonic stretch reflexes that results from a variety of disorders affecting the brain and spinal cord. Treatment of spasticity is generally considered when the increase in tone interferes with functional activities, such as positioning, mobility, or daily cares, when it is painful, or when it leads to complications such as contractures or skin breakdown. This review discusses the pathophysiology of spasticity and details the various treatments av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
6

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 86 publications
0
10
0
6
Order By: Relevance
“…18,19 Treatment of spasticity is considered when it interferes with function, such as ambulation, transfers, and ADLs, or is painful. 4 Conservative interventions, such as physical therapy, splints, and orthoses, are often prescribed initially; however, when these measures are ineffective, medications are often necessary.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…18,19 Treatment of spasticity is considered when it interferes with function, such as ambulation, transfers, and ADLs, or is painful. 4 Conservative interventions, such as physical therapy, splints, and orthoses, are often prescribed initially; however, when these measures are ineffective, medications are often necessary.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 In addition, baclofen causes muscle weakness, especially at moderate and high doses, which is of obvious concern in stroke patients who are hemiparetic. 4 Studies have reported that Ͼ10% of patients discontinue baclofen therapy because of muscle weakness. 24 Benzodiazepines, such as diazepam and clonazepam, reduce muscle tone and painful spasms by increasing the affinity of GABA receptors for endogenous GABA, predominantly at the spinal cord level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations